Teacher trainers and Master students’/ in-service teachers’ perspectives of the needed competencies for English language teachers: A survey at the University of Languages - Trần, Minh Hằng (ĐHNN, 2017)
English language teachers who hold an essential role in education system are expected to be highly competent in order to enhance th e student learning outcomes. Hence, improving teachers‘ competence has been considered one of the key factors of educational reforms in many countries, including Vietnam. To address this issue, the initial task is to identify the training needs as well as the strengths and weaknesses of the English language teachers. This study aims to investigate professional competence and training needs of the in - service English language teachers – MA students at ULIS, VNU. The data were collected from interviews with th ree teacher trainers, and survey questionnaires with 65 English language teachers. The results showed that the majority of the English teachers had high training needs in most competencies. Furthermore, beside the positive perceptions of their own competen ce, the targeted teachers had some challenges in reaching professionalism. It is of great importance for the teachers in this study to be aware of the gap between theoretical knowledge and practical knowledge. On this basis, the study recommends a number o f directions for the targeted teachers to help them be more qualified. It is hoped that the findings can be used as a good source of professional development materials not only for the targeted teachers but also for the language policy makers in education.